Unravelling high insect diversity and community turnover along a tropical-temperate elevation gradient: A metabarcoding approach - Damián Villaseñor-Amador; Pilar Benites; Fatima M. Sandoval-Becerra; Madai Rosas-Mejía; Alejandro Zaldívar-Riverón; Milan Janda (PLoS ONE, 2025)
The transition zone between the Nearctic and Neotropical biogeographic regions is one of the most species-rich areas of North America, known as the Mexican Transition Zone. We sampled mobile insects along a 2000 m elevational gradient for 13 months using flight interception traps (Malaise) to evaluate their diversity, community structure and environmental factors linked to their distribution. We identified 3091 Molecular Operational Taxonomical Units (560 ± 199 SD per trap), out of which 513 were identified to genus and 197 to species. Our results show high turnover at both species and genus levels across the elevational gradient. Elevational diversity patterns varied across taxa: Coleoptera and Lepidoptera showed their highest diversity at mid-elevations, while Diptera and Hymenoptera had increased diversity with elevation. Temperature and vegetation composition best explained the spatial fluctuations of insect diversity. Our work represents the most comprehensive survey of insect communities in the region to date. By combining a long-term survey with high-throughput metabarcoding, this study provides an overview of regional diversity and establishes a foundation for detailed follow-up studies.